(untitled) (IAHS Medical Journal, 2022)
Background: Cervical cancer belongs to a glorious natural history which favors well implemented secondary prevention. Considering the various constraints in our country, our study aimed to evaluate Visual Inspection of Cervix with Acetic Acid (VIA) as an alternative or adjunct to cervical cytology (Pap smear) in early detection of cervical cancer and also to assess its effectiveness as a screening method in a tertiary center outside of low resource settings. Materials and methods: This cross-sectional descriptive study was carried out at Gynae OPD of Chittagong Medical College Hospital (CMCH) from January to December 2012. A total of 1600 sexually active women with 21 to 60 years old were enrolled in this study by purposive sampling technique. The women underwent a complete clinical evaluation, including Pap smear and VIA. Any positive test was referred to colposcopy and directed biopsy. Finally, data were analyzed with the help of SPSS 16 software. Results: Out of 1600, VIA was positive in 135(8.4%) and cytology was positive in 74(4.6%) cases of the true positive 48 cases. The sensitivity of VIA (75%) was much higher than that of Pap smear (48%). The sensitivity ratio 1.54 (p<0.001). The positive predictive value for detection of CIN2 and above was 17% for VIA and 16% for pap (p=0.5). Moreover, patients of lost to follow-up before colposcopy and biopsy were only 4.44% with VIA positive cases while 28.38% with positive Pap smear (p<0.0001). Conclusions: The high sensitivity of VIA indicates that it may be a feasible alternative test for detection of precancerous lesions of the cervix not only in limited-resource settings but also in a well-equipped tertiary hospital. IAHS Medical Journal Vol 4(1), June 2021; 22-26